Local and systemic morbidities of de novo metastatic prostate cancer in Singapore: insight from 685 consecutive patients from a large prospective Uro-oncology registry. Issue 2 (18th February 2020) - Tan, Yu Guang; Pang, Leonard; Khalid, Farhan; Poon, Randy; Huang, Hong Hong; Chen, Kenneth; Tay, Kae Jack; Lau, Weber; Cheng, Christopher; Ho, Henry; Yuen, John
Abstract : Objective: To evaluate the incidence and management of local and systemic complications afflicting patients with de novo metastatic prostate cancer (mPCa) in Singapore. Design: Retrospective analysis of a large prospective Uro-oncology registry of mPCa. Setting: This study is carried out in a tertiary hospital in Singapore. Participants: We reviewed our institution's prospectively maintained database of 685 patients with mPCa over a 20-year period (1995–2014). Patients with non-mPCa or those progressed to metastatic disease after previous curative local treatments were excluded. Primary and secondary outcome measures: The primary outcome was to evaluate the systemic and local morbidity rates associated with mPCa. Local complication was defined as the need for palliative procedures to relieve urinary obstruction, worsening renal function or refractory haematuria, while systemic complication was related to radiographic evidence of skeletal-related pathological fractures. Secondary outcomes analysed were the management and overall survival patterns over 20 years. Results: 237 (34.6%) patients required local palliative treatments. 88 (12.8%) patients presented with acute urinary retention, 23 patients (9.7%) required repetitive local palliative treatments. On multivariate analyses, prostate-specific antigen >100 (p=0.02) and prostate volume >50 g (p=0.03) were independent prognostic factors for significant obstruction requiring palliative procedures. 118 (17.2%) patients developed skeletal fractures, with poor Eastern Cooperative Oncology Group Performance (ECOG) status (p=0.01) and high volume bone metastasis (p<0.01) independently predictive of skeletal fractures. Altogether, 653 (95.3%) patients received androgen deprivation therapy (ADT), with the median time to castrate resistance of 21.4 months (IQR 7–27). The median overall survival was 45 months (IQR 20–63), with prostate cancer mortality of 81.4%. Improved overall survival was observed from 41.6 months (1995–1999) to 47.8 months (2010–2014) (p<0.01). Conclusion: Morbidities and complications arising from mPCa are more common and debilitating than we thought, often requiring immediate palliative treatments, while many necessitate repeated interventions with progression.